OS3.1 IDH-wild type grade II gliomas: a retrospective series of AINO (Italian Association of Neuro-Oncology). (19th September 2018) - Bruno, F; Silvani, A; Ius, T; Bello, L; Minniti, G; Pace, A; Lombardi, G; Soffietti, R; Rudà, R
Abstract: Background: Information regarding clinical characteristics and response to treatments of IDH-wild type grade II gliomas is still lacking. This national retrospective study aimed to investigate natural history, management, and factors affecting response to treatments and outcome of a cohort of WHO grade II IDH-wild type glioma patients. Material and Methods: We collected all clinical data of patients diagnosed with WHO grade II IDH-wild type glioma from 1999 to 2017 in six major Italian Institutions. IDH mutation was assessed by either immunohistochemistry or sequencing (in cases with negative immunohistochemistry). Exclusion criteria were the presence of minimal anaplastic foci or radiological features of HGGs. Kaplan-Meier curves and Cox-regression models were used for univariate and multivariate analysis. Results: Overall, 194 patients were collected and ultimately 122 met the inclusion criteria. Median age was 45 years. Seizures were the presenting symptoms in 74 cases (60.7%), while focal deficits were present in 25 cases (20.5%), and 5 patients (4.1%) had an incidental radiological diagnosis. Non-enhancing tumours on MRI accounted for 74% while 26% had minimal/mild contrast enhancement. Surgery consisted in gross total resection in 29%, partial/subtotal in 45%, biopsy in 24%, and unknown in 2%. According to WHO 2007 astrocytomas were 44%, oligodendrogliomas 35%, and mixed gliomas 21%. MGMT methylation was available in 68% of patients, and in 40% of them was methylated. Post-surgical management consisted in watch and wait in 42%, chemoradiation in 21%, chemotherapy alone in 21%, radiotherapy alone in 5%, radiotherapy followed by chemotherapy in 5%, and 6% unknown. Radiological response to first line treatment was available according to RANO criteria in 47 cases: stable disease was observed in 23 patients (48.9%), progressive disease in 16 (34.0%), partial response in 7 (14.9%), and complete response in 1 (2.1%). Median time of follow-up was 31 months. Median PFS at first recurrence from diagnosis was 24.0 months (1.2 - 147.0). Treatments at the recurrence were second line chemotherapy in 33 cases (42.3%), second surgery in 18 cases (23.1%), radiotherapy in 10 cases (10.4%), and palliative care in 13 cases (16.7%) - we miss information about 4 patients. Median OS was 45.3 months (1.0 - 225.6). Factors positively associated with PFS and OS in univariate analysis were younger age, absence of contrast enhancement, and gross total resection. Age and extent of surgery retained a statistically significant importance in multivariate analysis. Conclusion: WHO grade II IDH-wild type gliomas have a worse outcome as compared with IDH-mutant tumours. This is the first study that details clinical and radiological presentation of this rare subgroup of tumours and suggests that gross total resection is critical in improving survival.